SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN INSTRUKTUR FITNESS MENERAPKAN METODE ADDITIVE RATIO ASSESSMENT (ARAS) (STUDI KASUS : VIZTA GYM MEDAN) - Hasmi, Mentari Ananda; Mesran, Mesran; Nadeak, Berto (STMIK Budi Darma, 2018)
Fitness instructor is someone who trains and gives direction to someone or a group of people who educate their clients (members), to help their clients achieve goals in terms of health, both physical and performance by exercising. Fitness instructors can also be called sports teachers. The obstacle faced at the time of acceptance of the Fitness Instructor is that the recruitment process is still done manually by looking at the data reports of prospective Fitness Instructors. Another obstacle is that the Fitness Instructor recruited does not have the quality capabilities desired by fitness owners. To overcome the selection process of Fitness Instructors who experience these obstacles by using an application called the Decision Support System. Decision Support Systems in determining the acceptance of Fitness Instructors can be generated based on several criteria in determining a criterion made to prevent mistakes made by certain parties. ARAS (Additive Ratio Assessment) is a comprehensive framework method of consideration of hierarchical processes which is then calculated by weighting to calculate a criterion in determining the acceptance of a Fitness Instructor.Keywords: Fitness Instructor, Decision Support System, Additve Ratio Assessment (ARAS)